2018
DOI: 10.21608/jappmu.2018.38895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tannin Protected Sunflower Meal without or with Chamomile Flowers Supplementation on Productive Performance of Zaraibi Dairy Goats and their Offspring

Abstract: This study aimed to investigate the effect of treated sunflower meal with 2% condensed tannins (Quebracho tannins, QT; Unitan, Argentina) or/and Chamomile Flowers supplementation on productive performance of Zaraibi dairy goats and their offspring. A feeding trial was conducted using twenty pregnant goats at the 3 rd and 4 th parities and initial body weight 35.55 ± 0.62 kg at the last month before parturition and lasted for 90 days after parturition. Animals were divided into four similar groups (n=5does/each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Research conducted on goats has demonstrated that the inclusion of herbal supplements in their diets has a beneficial impact on their digestive processes. The findings of current study align with previous research conducted by Hussein et al (2018), who found that supplementing lactating Zaraibi goats with 0.25% Chamomile flowers resulted in significantly higher digestibility of nutrients and improved feeding values compared to the control group (p<0.05). Similarly, EL-Basiony et al (2015) observed that lactating Damascus goats exhibited significantly enhanced nutrient digestibility coefficients when supplemented with 4.0 g/head/day of Echinacea purpurea (p<0.05).…”
Section: Digestibility and Feeding Valuessupporting
confidence: 91%
See 2 more Smart Citations
“…Research conducted on goats has demonstrated that the inclusion of herbal supplements in their diets has a beneficial impact on their digestive processes. The findings of current study align with previous research conducted by Hussein et al (2018), who found that supplementing lactating Zaraibi goats with 0.25% Chamomile flowers resulted in significantly higher digestibility of nutrients and improved feeding values compared to the control group (p<0.05). Similarly, EL-Basiony et al (2015) observed that lactating Damascus goats exhibited significantly enhanced nutrient digestibility coefficients when supplemented with 4.0 g/head/day of Echinacea purpurea (p<0.05).…”
Section: Digestibility and Feeding Valuessupporting
confidence: 91%
“…In contrast, El-Kholany et al (2015,2017) concluded that Baladi cows exhibited similar dry matter intake when their diets were supplemented with two levels of Chamomile flowers (5 or 10 g/100 kg BW/day) compared to the control ration. Furthermore, Hussein et al (2018) investigated the dry matter intake of Zaraibi dairy goats and found that supplementation with 0.25% Chamomile flowers did not significantly impact their intake. Likewise, Wu et al (2018) reported that lambs supplemented with 100 mg/kg BW/day of Echinacea exhibited similar average dry matter intake compared to those fed the control ration.…”
Section: Feed Intake and Water Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase (p≤ 0.01) were observed in serum cholesterol concentration in T3 (185.18 mg /dl) compared T1 and T2 which was (114.71 and 133.74) mg /dl respectively. These results resemble those of Al-Mallah (2007) who found that feeding lambs on diets treated with formaldehyde led to an increase in the urea concentration compared to the non-treatment, other studies (Hussein et al, 2018, Abdel-Ghani et al, 2011 indicated that feeding lambs on a low degradable sunflower meal or feeding with different levels of undegradable protein showed a significant decrease in blood urea concentrations. Also, studies of (Majewska et al, 2016, Radmanesh et al, 2015, Hadipour et al, 2014, found that feeding lambs on undegradable fat led to an increase in the concentration of cholesterol in the blood plasma.…”
Section: Introductionsupporting
confidence: 84%
“…In addition, Abo El-Fadel and Ashmawy (2015) observed that the protected linseed meal and cotton seed meal at 2% resulted in better economic evaluation expressed as economic return. Recently, Hussein et al (2018) reported that feed cost was higher in diet contained untreated Sunflower meal than that contained protected Sunflower meal by Tannin.…”
Section: -Economic Efficiencymentioning
confidence: 99%